Spatial And Temporal Distribution Of Macrophytes In Relation To Water Quality Parameters In Chenderoh Reservoir, Perak - Ismail, Siti Norasikin (2021)
A study on the spatial and temporal variations of environmental factors and the distribution of macrophytes at Chenderoh Reservoir was carried out from June 2015 until May 2016. This study was aimed to analyze the diversity and distribution pattern of macrophyte species based on spatial and temporal factors in relation to water quality parameters and reservoirs morphometry. The field sampling was conducted at 18 sampling points covering the embayments and main river channel of the reservoir with an interval of 1 km. Surveys on the macrophyte species distribution and cover percentage were conducted based on line transect and quadrat methods. Several parameters of water quality from three different depths (surface, Secchi depth and bottom) were measured in-situ and water samples were collected for further analysis. In the laboratory, the analysis of total suspended solids (TSS), chlorophyll a (Chl a), orthophosphate (PO4), nitrite-nitrogen (NO2), nitrate-nitrogen (NO3) and ammonia-nitrogen (NH3) were carried out. Bathymetric survey was conducted in February 2016 and April 2017 using echo sounding method. In this study, macrophyte species was distributed according to the slope of the reservoir. A total of 34 macrophyte species from four different types; emergent, floating-leaved, submerged and free-floating were recorded. Eichhornia crassipes and Salvinia adnata were recorded at all sampling points and SP5 resulted in the highest species number with 29 species.